What cases are to be heard by the Appellate Division and why: Noor Azlin bte Abdul Rahman and another v Changi General Hospital Pte Ltd [2021] 2 SLR 440 - NAI, Grace Jin Yi (Institutional Knowledge at Singapore Management University, 2023)
On 2 January 2021, certain statutory amendments came into effect: specifically, the Supreme Court of Judicature (Amendment) Act 2019 (Act 40 of 2019) (“SCJ(A)A”) which amended the Supreme Court of Judicature Act (Cap 322, 2007 Rev Ed) (“SCJA”), and the Rules of Court (Amendment No. 5) Rules 2020 (“ROC(A)”) which amended the Rules of Court (Cap 322, R 5, 2014 Rev Ed) (“ROC”). These amendments had a significant impact on the court appellate system. For clarity, the pre-2 January versions of the legislation will be referred to as the “former SCJA” and “former ROC”, while the post-2 January versions will be referred to as the “amended SCJA” and “amended ROC”.